THE FUTURE OF FORMATIVE ASSESSMENT: LEVERAGING AI FOR CONTINUOUS LEARNING EVALUATION - Nurul Lutfiah Nusi; Nomsa Zulu; Mujahid Damopolii (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2026)
The integration of Artificial Intelligence (AI) in education has the potential to revolutionize formative assessment practices by offering real-time, personalized feedback. Formative assessment, traditionally seen as an ongoing process to monitor student progress, faces challenges such as scalability and timely feedback. AI-powered systems can provide instant insights into student performance, facilitating continuous learning evaluation. This research aims to explore how AI can enhance formative assessment by providing continuous and individualized evaluation of students’ progress. A mixed-methods approach was employed, using surveys, interviews, and classroom observations across five schools that have implemented AI-based learning platforms. The results revealed that AI-driven formative assessments significantly improved student engagement and performance, with 80% of teachers reporting more efficient monitoring and intervention strategies. However, concerns about the depersonalization of feedback and the risk of over-reliance on AI were noted, suggesting the need for a balance between technological tools and human interaction. The study concludes that AI has the potential to transform formative assessment practices but requires careful integration into teaching methods to ensure it complements rather than replaces teacher-student interactions.